Review of The Psychological Thinking of Ibn Rusyd - Waty, Dwi Septiana Khofida; Soleh, Achmad Khudori (International Journal Labs, 2023)
Ibn Rushd is a thinker who contributed many of his works to the development of science, especially in the field of philosophy. However, there is not much research that discusses Ibn Rushd in his psychological studies. Even though Ibn Rushd's interpretation in the field of psychology is written in his work entitled De anima. The purpose of this study is to find out what Ibn Rushd thinks about several scientific studies, especially in the field of psychology. The method used in this research is library research, the data sources in this study are several articles and journals that focus on Ibn Rushd's psychological thinking, and data analysis techniques in this study use the literature study method. The results of this study conclude that Ibn Rushd's thoughts in Islamic psychology explain that in the soul there is a heart, eve, and reason. In the structure of the soul, there is a heart which is the form of interaction between hawa and reason, where it will follow the dominance of one of them. Nafs/soul in its level is divided into three, namely nafs-muthmainnah, nafs-lawwamah, and nafs-anger. The reason according to Ibn Rushd is a place that will accommodate all forms of knowledge through thinking power (external senses), imagination power (internal senses), and intellectual power (ratio power) to know the truth about the nature of God and the universe there are many ways that can be done. One way to do this is through Islamic education.